The polar lichens Caloplaca darbishirei and C. soropelta highlight the direction of bipolar migration - Søchting, Ulrik; CASTELLO, Miris (Polar Biology, 2012)
A proper phytogeographic affiliation of Antarctic lichen species has become feasible using molecular phylogeographic methods. Caloplaca citrina is a heterogeneous taxon including several species which occurs in polar regions and is common in Antarctica. Collections of C. citrina from the Antarctic were revised using morphological, anatomical and molecular characters (ITS). They were found to belong to two species: Caloplaca darbishirei (C.W. Dodge & G.E. Baker) Cretz. and C. soropelta (E.S. Hansen, Poelt & Søchting) Søchting. The molecular phylogeny showed them to be sister species, but well separated. Morphological and chemical characters, ecology and distribution of the species are discussed. C. darbishirei is the most common species in the Antarctic, and it is so far known only from Antarctica and Southern South America. C. soropelta, reported here as new to South America, is a bipolar species with all close relatives in the Southern Hemisphere; it is therefore most likely that the species colonized the Arctic from the south. C. citrina s. str. is not confirmed to occur in Antarctica. The study emphasizes the suitability of genotyping for understanding the taxonomy and phylogeography of bipolar lichens.